RESHAPING THE HOMOSEXUAL IDENTITY OF MIDDLE-AGED GAY MEN IN AMERICA: A SOCIOLOGICAL STUDY OF IDENTITY PROCESS ON ANDREW SEAN GREER’S LESS - Fairuz Su'da; Muh Arif Rokhman (Rubikon : Journal of Transnational American Studies, 2020)
The detrimental effects caused by the LGBT victimization in America are directly felt by middle-aged homosexuals nowadays and is internalized into their identity, creating problems that continuously affect them even after LGBT acceptance in the United States. The shift of homosexual identity in middle-aged American homosexuals is thus inevitable in order to regain their identity balance. Andrew Sean Greer’s Less depicts this issue through the internal conflicts of Arthur Less —a character struggling to accept his identity as an aging homosexual man. Arthur’s process in assimilating new experiences around him and accommodating his conceptionabout his homosexual identity become the highlights of this study. The writer utilizes Susan Krauss Whitbourne’s Identity Process Theory that deals with identity assimilation, identity accommodation, and identity balance. The result shows that past LGBT victimization has caused (1) HIV/AIDS trauma, (2) hyper-sexualized image, (3) cynicism towards marriage, and (4) internalized homonegativity, all of which creating the balance disruption on identity. When identity assimilation fails and identity accommodation occurs, middle-aged American homosexuals are encouraged to acknowledge that (1) homosexual identity exists beyond stereotyped sexual context, (2) there are no standardized attitudes that they must adopt, and (3) they are allowed to desire the same sense of comfort and intimacy through committed relationship or marriage, like their heterosexual counterparts.